Behavioral and pharmacological characterization of planarian nociception - Reho, Guillaume; Menger, Yannick; Goumon, Yannick; Lelièvre, Vincent; Cadiou, Hervé (Frontiers in Molecular Neuroscience, 2024)
Introduction Pain mostly arises because specialized cells called nociceptors detect harmful or potentially harmful stimuli. In lower animals with less convoluted nervous system, these responses are believed to be purely nociceptive. Amongst invertebrate animal models, planarians are becoming popular in a wide range of pharmacological and behavioral studies beyond the field of regeneration. Recent publications led the way on pain studies by focusing on nociceptive behaviors such as the ‘scrunching’ gait displayed under various noxious stimuli, as opposed to the ‘gliding’ gait planarians usually adopt in normal conditions. Methods In this study, we adapted commonly used nociceptive tests to further explore nociception in planarians of the species Girardia dorotocephala. By using behavioral analysis in open fields and place preferences, we managed to set up chemical, thermal and mechanical nociceptive tests. We also adapted RNA interference protocols and explored the effects of knocking down TRPA1 ion channels, one of the main effectors of chemically and thermally-induced nociceptive responses in vertebrates. Results Consequently, we demonstrated the reliability of the scrunching gait in this planarian species, which they displayed in a dose-dependent manner when exposed to the irritant AITC. We also showed that suppressing the expression of TRPA1 ion channels completely suppressed the scrunching gait, demonstrating the involvement of TRPA1 nociceptors in this nociceptive reaction. Besides, we also explored the effects of two common analgesics that both displayed strong antinociceptive properties. First, morphine reduced the chemically-induced nociceptive scrunching gaits by more than 20% and shifted the EC50 of the dose–response curve by approximately 10 μM. Secondly, the NSAID meloxicam drastically reduced chemically-induced scrunching by up to 60% and reduced heat avoidance in place preference tests. Discussion Thus, we managed to characterize both behavioral and pharmacological aspects of G. dorotocephala’s nociception, further developing the use of planarians as a replacement model in pain studies and more globally the study of invertebrate nociception.